The Development of the Sihali Aek Ceremonial Tradition in Tipang Village, Baktiraja District (2013–2024) - Harry Kriston Situmeang; Ammar Zhafran Ryanto; Sintia Harnum; Mahya Atalia Sinaga (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
This study examines the development of the Sihali Aek ritual tradition in Tipang Village, Baktiraja Subdistrict, Humbang Hasundutan Regency, from 2013 to 2024. The Sihali Aek tradition is a customary ritual of the Batak Toba people related to prayers for soil fertility, the flow of water sources, and community well-being, particularly in the agricultural sector. This study aims to understand the background of the emergence of the Sihali Aek tradition, the process of conducting the ceremony, and the development of this tradition in the daily lives of the people of Tipang Village. The research method employed was a qualitative approach with a historical perspective, utilizing data collection techniques such as observation, interviews, and documentation. The results indicate that the Sihali Aek tradition holds significant social, religious, and cultural value for the community. Over time, the tradition has undergone several changes in its implementation, yet it continues to preserve the customary values that define the identity of the Batak Toba people.